Theological Issues of Sexuality and Christian Marriage - Nainggolan, Parlaungan; Rogate Artaida Tiarasi Gultom; Dapot Damanik (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Sexuality and marriage are two important aspects of human life that have a deep spiritual dimension in the context of Christian faith. However, social, cultural, and technological developments in the modern era have presented various issues that challenge the church's traditional views on these two things, such as free sex, same-sex marriage, divorce, and interfaith marriage. This study aims to examine theologically and pastorally the Christian view of sexuality and marriage based on the Bible, and to identify the church's response to contemporary dynamics and challenges. The research was conducted using a literature study method and a contextual hermeneutic approach, and considered interdisciplinary perspectives from the fields of sociology and psychology. The results of the study indicate that the church needs to formulate an approach based on love and biblical truth in dealing with modern issues, as well as strengthen pastoral care and faith education in Christian families. Thus, a deep and relevant understanding of faith can be the basis for guiding people to live a holy sexual and marital life in the midst of a changing world.